Virus Bakteri sebagai Terapi untuk Penyakit Infeksi - Rina Hidayati Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to provide information related to the role of phages or bacterial viruses in treating infectious diseases. The method used is a secondary literature study from several research publications. The results showed that phage therapy had been medically proven to be superior to antibiotic treatment. Phage families Myoviridae and Podoviridae are the best candidates for phage therapy because most of them have a lytic cycle. Phages with lytic phage types tend to be widely used as biocontrol agents because they are specific and lyse target cells (pathogenic bacteria). In addition, phages do not have genetic material that can be integrated into the human body, so therapy using phages is not virulent in humans. Treatment using phages also does not cause phage resistance to antibiotics. In conclusion, phages' advantages, effectiveness, and host specificity make phages used in various applications to treat infectious diseases. Keywords: Bacteriophage, Phage, Lytic, Therapy, Virus